Cài đặt các thuật toán bảo đảm tính nhất quán dữ liệu cho mô hình cơ sở dữ liệu quan hệ - Trung, Phạm Quang; Huy, Nguyễn Xuân (Journal of Computer Science and Cybernetics, 2016)
Data integrity preservation is an important ruequirement in designing databases satisfied to build normal forms of relational schemes. All algorithms that translate a form of  schema into a nomal form require to define keys of the schema. Therefore a key finding problem is very important for designing database. There have been many solutions for this problem. In this paper, we present a solution that base on the concept of translation of relational schemes, which translates the prime schema into the class of schemes that made key finding problem simpler. Basis factors of relational schema are an amount of attributes, of functional dependencies. That has concern with a completcity of closure, key, and cover finding problem… The purpose of the translation to simplify the prime schema by rejecting some attributes, which are not belong to  or are belong to all keys of prime schema is the result after adding with a set of  attributes belong DABASCHE that is a solution of  implementation of that algorithm. We present some important  functions of the module DABASCHE for designing relational databases and it’s basic data structures in the language that simulates the Pascal programming language.